Inequality, worker mobilisation and lessons from history: Australia 1788-1900. (2nd January 2023) - Quinlan, Michael; Maxwell-Stewart, Hamish
ABSTRACT: Neoliberalism has wrought fundamental changes in the world of work, leading to rising inequality, substantial weakening of organised labour and a decline in industrial relations as a field, especially in relation to teaching. Drawing on historical 'big data' this paper argues that examining the history of worker mobilisation provides a better understanding of these developments, including the importance of considering diverse forms of organisation and action as well as multi-pronged methods built around a key set of issues. It can also inform efforts to address challenges posed by neoliberalism. We conclude by arguing that an historical perspective can better equip the field of industrial relations to meet challenges extending beyond the world of work.